The Sufi Sheikhs and their Socio-cultural Roles in the Islamization of Bengal during the Mughal Period (1526-1858) - Wahyuddin Halim (Universitas Islam Negeri Alauddin Makassar, 2018)
One of the most observable influences of Islam on the Indian-subcontinent, especially in today’s Bangladesh, is the spiritual and humane teaching of Sufism during the medieval period. Based primarily on a critical elaboration of Eaton’s The Rise of Islam in Bengal Frontier 1204-1760 (1993), this article attempts to describe the socio-cultural and religious role of the Sufi sheikhs in the conversion to Islam of the Bengali people during the period of Mughal Empire (1526-1858). The earliest Sufis attempted at Islamic conversion began in the very hostile environment maintained by the local Hindu or Buddhist rulers. However, these Sufis sheikhs or pirs were able to convert most of the local population to Islam by preaching about the great teachings of the new religion about love, brotherhood, and equality. Among other success factors in the Sufi mission in Islamic conversion of the Bengali during the period under discussion were their unconquerable dedication and exceptional piety as well as the common belief among the Bengali people that these pirs could perform incontestable miracles.